The influence of special acrobatic classes on the expression levels of sustainability of the vestibular analyzer of young 6-8 year-old all-round fighters attending basic training groups - Voropay, S.M.; Buryanovatiy, O.M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to increase the level of manifestation sustainability of the vestibular analyzer young fighters-all-rounders aged 6-8 years in initial training through a shift from the technical and tactical training in the direction of general physical and acrobatic. The research task was to prove the effectiveness of training, aimed at special acrobatic training at the level of the manifestation of stability of the vestibular analyzer young fighters-all-rounders aged 6-8 years who are engaged in military-sports-around in initial training. Material : the research has been done at the premises of the Kirovograd Federation of military and sports all-rounders. It covered 40 young sportsmen divided into two groups of 20 persons each: an experimental and control group. The research was conducted during the two years engaging steady student population. Results : it is established that after the execution of the experimental training program most likely changes were observed among the indicators vestibular illusions against rotation (VIAR) (43.3 %), after performing traditional training programs respectively to 10.6 %; less noticeable changes among the indicators heart rate and eyes nystagmus (2,6%, 1,62% and 0,4%). Conclusions : shifting focus from technical and tactical training in the direction of the general physical and acrobatic increase the level of manifestation of the stability of the vestibular young fighters all-rounders aged 6-8 years.